2020
DOI: 10.1136/gutjnl-2019-319990
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the complex interplay between pancreatic cancer, diabetes mellitus subtypes and obesity/BMI through causal inference and mediation analyses

Abstract: ObjectivesTo characterise the association between type 2 diabetes mellitus (T2DM) subtypes (new-onset T2DM (NODM) or long-standing T2DM (LSDM)) and pancreatic cancer (PC) risk, to explore the direction of causation through Mendelian randomisation (MR) analysis and to assess the mediation role of body mass index (BMI).DesignInformation about T2DM and related factors was collected from 2018 PC cases and 1540 controls from the PanGenEU (European Study into Digestive Illnesses and Genetics) study. A subset of PC c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 50 publications
2
54
0
Order By: Relevance
“…We also collected plasma samples from 130 participants in Spain as the external validation set, including early PDAC (Stage I/II, n = 37), advanced PDAC (Stage III/IV, n = 38), chronic pancreatitis (n = 19) and healthy controls (n = 36). Those participants were randomly selected from the European Study into Digestive Illnesses and Genetics (PanGenEU), a mostly hospital‐based case‐control study of pancreatic cancer conducted in six European countries (Spain, Germany, Ireland, the United Kingdom, Italy and Sweden) 17 . Cases diagnosed or suspected of having pancreatic cancer and the corresponding controls matched by region, sex and age (± 10 years) were included from 2007 to 2014.…”
Section: Methodsmentioning
confidence: 99%
“…We also collected plasma samples from 130 participants in Spain as the external validation set, including early PDAC (Stage I/II, n = 37), advanced PDAC (Stage III/IV, n = 38), chronic pancreatitis (n = 19) and healthy controls (n = 36). Those participants were randomly selected from the European Study into Digestive Illnesses and Genetics (PanGenEU), a mostly hospital‐based case‐control study of pancreatic cancer conducted in six European countries (Spain, Germany, Ireland, the United Kingdom, Italy and Sweden) 17 . Cases diagnosed or suspected of having pancreatic cancer and the corresponding controls matched by region, sex and age (± 10 years) were included from 2007 to 2014.…”
Section: Methodsmentioning
confidence: 99%
“…The interplay of T2DM to PDA is complex and, despite numerous studies, not comprehensively understood. However, strong existing evidence demonstrated that (new-onset) T2DM is likely to be a consequence of a tumor microenvironment consisting of progressively growing PDA cells 47 . We complement prior findings by showing that onset of T2DM is a potential sign of functionally shifting Langerhans islets towards shaping anti-tumor immunity via CCL27 production as a defense mechanism against PDA.…”
Section: Discussionmentioning
confidence: 99%
“…Among stromal cells, adipocytes could represent a potential source of NEAA including serine (Green et al 2016). The abundance of adipocytes in the pancreas increases in elderly, especially in the context of obesity and diabetes, which are risk factors for PDA (Molina-Montes et al 2020). M2 macrophages are the most abundant immune-related stromal cells found in PDA tumors.…”
Section: Discussionmentioning
confidence: 99%